2016
DOI: 10.1515/hmbci-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesaemia: a modifiable risk factor of diabetic nephropathy

Abstract: We concluded that hypomagnesaemia was significantly associated with higher prevalence of diabetic nephropathy and can be used as a marker for the risk of development of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In the present study, we also found that the serum Mg concentration of patients with T2DM and DN was significantly lower than that in healthy individuals. A recent study found that hypomagnesemia is associated with a high incidence of DN and is an independent predictor of DN (16), and others have shown that hypomagnesemia is associated with both the development and progression of DN (37,38).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we also found that the serum Mg concentration of patients with T2DM and DN was significantly lower than that in healthy individuals. A recent study found that hypomagnesemia is associated with a high incidence of DN and is an independent predictor of DN (16), and others have shown that hypomagnesemia is associated with both the development and progression of DN (37,38).…”
Section: Discussionmentioning
confidence: 98%
“…Mg deficiency leads to impaired glucose tolerance, insulin resistance, abnormal lipid metabolism, and OS (10). Previous studies have shown that the prevalence of hypomagnesemia in patients with DN is significantly higher than that in those without (16). In addition, Mg deficiency leads to the opening of L-type calcium (Ca 2+ ) channels in macrophage, which increases the intracellular Ca 2+ concentration and promotes the release of pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Similar beneficial effects of oral magnesium have been demonstrated in people with type 2 diabetes and hypomagnesemia [ 71 ]. An observational study concluded that low serum magnesium was significantly associated with higher prevalence of diabetic nephropathy, and hypomagnesemia can be used as a marker for the risk of development of diabetic nephropathy [ 72 ]. Additionally, hypomagnesemia was associated with poor glycemic control [ 73 ], reduced HDL cholesterol, increased triglycerides, and total cholesterol levels [ 74 , 75 ].…”
Section: Hypomagnesemia and Endocrine Diseasesmentioning
confidence: 99%
“…It is therefore of interest that recent meta-analyses and cohort studies have pointed to an inverse relationship between magnesium consumption and the incidence of NIDDM / metabolic syndrome (95,(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121) and that a recent prospective randomized controlled trial has demonstrated enhanced insulin sensitivity in a population of 128 obese patients with confirmed hypomagnesemia, chronic renal impairment and impaired glucose tolerance, in response to magnesium supplementation (365 mg per day for three months duration) (122). A similar study in a smaller sample size (n=72) of obese patients with metabolic syndrome, confirmed reduced baseline intracellular (monocyte) magnesium concentrations in 36% of obese patients but did not report any improvement in markers of insulin resistance in response to magnesium supplementation (400 mg per day for three months duration), however potential compliance issues and a small study sample render these results less reliable (123) Overall, when thiamine deficiency is considered with magnesium, it is likely that the deficiency of one or both may affect the other and compromise glucose metabolism in the obese patient.…”
Section: Thiamine and Magnesiummentioning
confidence: 99%